Adakah Pengaruh Organizational Support, Ethical Climate, dan Quality of Work-Life terhadap Job Satisfaction? - Nabilla Baina; Tiarapuspa (Jurnal EMT KITA, 2023)
Negative or positive perceptions about the employee's work are reflected in the perceived level of job satisfaction.  The challenge for human resources (HR) managers is to support programs and initiatives that increase the job satisfaction of their staff members.  Therefore, this research uses organizational support, ethical climate, and quality of work-life for as the variables that affect job satisfaction. Data related to a sample of 173 students of one of the universities in Jakarta, Indonesia who are already working. The data were obtained using a questionnaire, which was then carried out validity tests and reliability tests as well as structural equation modeling (SEM) using SPSS software version 25 and AMOS version 24. The results showed that the positive influence of ethical climate, and quality of work-life that was felt on job satisfaction was supported.